A Proposal to Select Modern Financial Instruments for Financing Large-Scale Projects for Thailand’s State-Owned Enterprises - sukcharoensin, sorasart (Journal of Applied Economics and Management Strategy, 2025)
This paper proposes a process for selecting funding sources through traditional financial markets and modern financial instruments under a government policy framework. Several elements such as project types, project importances, financial market conditions and the debt capacity has been synthesized to form a basic guideline for selecting modern financial instruments for Thailand’s state-owned enterprises to be used as a preliminary approach in obtaining appropriate sources of funds under the current environment and constraints.